Resistance Dynamics of Gendered Subalterns in Yug Pathak’s Urgenko Ghoda - Rai, Bidur (Dristikon: A Multidisciplinary Journal, 2023)
This paper explores how Mhendo resists the dominant culture and hegemonic ideology in Yug Pathak’s “Urgenko Ghoda”, published in 2066 BS, using a perspective of resistance as a theoretical framework. The objectives of the study are to examine how marginalized people oppose the dominant culture by participating in the armed revolution. The central character, Mhendo in the novel has a firm belief in the glories of the Tamang history. She learns that the ruling class conquered the Tamang warriors and subjugated them. They have become victimized on their own land. She figures out the reasons behind the misrepresentation of the people and the community as she has grown up with the Tamang myth in Ichong. This provokes her ethnic consciousness and prepares her to resist in an attempt to regain the lost history. Her decision to recruit herself in the decade-long civil war is a form of resistance to cultural hegemony. The paper writer uses here the concepts of influential critics such as Margaret S Archer, Kasper Masse, Miguel Tamen, Jocelyn A. Hollander and Rachel L. Einwohner and Gayatri Chokravorty Spivak as a theoretical framework. Spivak interrogates the concept of the colonial subject in postcolonial discourse and limits the ability to relate with diverse cultures, Similarly, Miguel Tamen believes that the attempt to critique and interpret is to express resistance.